Identification of soil varieties in the Dujail district (Journal of the College of Basic Education, 2019)
Administratively, the study area is located within Salah al-Din Governorate, with an area of ​​about (1285 km2). The most important natural characteristics were represented by the geological structure, climate and soil. The rocks of Lake Tharthar, while the quadrilateral time deposits represented by the Pleistocene and Holocene, which included several deposits (placer fan deposits, sulfur deposits, flood plains, valleys-filled sediments). The terrain is relatively flat, with elevations ranging from (35 m) along the southern parts of the region, and (75 m) in the northeast part of the region, near Lake Tharthar. Climatologically, the data of the Samarra plant are based on climatic elements (maximum temperature, minimum temperature, wind speed and rainfall). The soil in the region was (6) varieties (soil plains old river embedded in silt, the soil of the old river plains gravel, soil soils, gypsum gravel soil, desert gypsum soil, bottom soil of the valley). The physical and chemical characteristics of the soils were determined based on (6) samples of soil sections, whose depths ranged between (40-50 cm). And drop the data on a map.